OER AWARENESS AND USAGE AMONG OPEN AND DISTANCE LEARNING STUDENTS IN SOUTH-WESTERN NIGERIA - Sunday Abidemi Itasanmi (Sanata Dharma University Yogyakarta, 2020)
This study assessed Open Educational Resources (OER) awareness level and usage among Open and Distance Learning (ODL) students in South-western Nigeria. A descriptive research design was adopted for the study. Three ODL institutions (University of Ibadan Distance Learning Centre, National Open University of Nigeria, Ibadan Study centre and University of Lagos Distance Learning Institute) were purposively selected. A structured questionnaire titled